Combination of factor Xa inhibition and antiplatelet therapy after stenting in patients with iliofemoral post-thrombotic venous obstruction. (July 2016) - Langwieser, Nicolas; Bernlochner, Isabell; Wustrow, Isabel; Dirschinger, Ralf J; Jaitner, Juliane; Dommasch, Michael; Bradaric, Christian; Laugwitz, Karl-Ludwig; Ibrahim, Tareq
Objectives: Studies addressing optimal postprocedural pharmacological management after endovascular stenting of iliofemoral post-thrombotic venous obstruction are lacking. We report our early clinical experience with a combination of rivaroxaban and clopidogrel in patients after iliofemoral post-thrombotic venous obstruction stenting. Methods: Demographic, procedural, and follow-up data of nine patients (seven women; mean age of 32 ± 11 years) undergoing 10 procedures for iliofemoral post-thrombotic venous obstruction performed between August 2012 and January 2014 were retrospectively reviewed. After endovascular intervention, all patients were administered 20 mg rivaroxaban once daily (s.i.d.) and 75 mg clopidogrel s.i.d. or every second day depending on the individual drug responsiveness for at least six months. The adenosine diphosphate-induced platelet aggregation (platelet aggregation, in aggregation units × min) was assessed on a Multiplate analyzer. Patency was verified venographically at procedure end and was evaluated with duplex ultrasound in regular follow-ups. Results: Iliofemoral venous flow was successfully re-established by percutaneous endovascular angioplasty and stent implantation in nine left-sided and one bilateral iliofemoral post-thrombotic venous obstruction. Under dual treatment strategy of rivaroxaban and clopidogrel with platelet aggregation control (median (range): 285 aggregation units × min (192; 402)), none of the patients experienced restenosis or stent thrombosis, respectively. After a median follow-up of 14 months (range: 6–26 months), the primary patency rate was 100% and no in-stent restenosis, stent occlusion or relevant minor or major bleeding occurred. Conclusion: Combined factor Xa inhibition and tailored antiplatelet therapy after stenting of iliofemoral post-thrombotic venous obstruction were safe and performed favorably in terms of vessel patency.